2019
DOI: 10.1021/acsmacrolett.9b00120
|View full text |Cite
|
Sign up to set email alerts
|

Functionalizable, Side Chain-Immolative Poly(benzyl ether)s

Abstract: Herein, we report a poly­(benzyl ether)-based self-immolative polymer (SIP) with pendant pyridine disulfide groups. Cleavage of the side-chain disulfides leads to the formation of phenolates, which initiate depolymerization from the side chain. Due to the higher density of the disulfide groups compared to that of the chain-end-capping group, which normally is responsible for initiating depolymerization of SIPs, the side chain-immolative polymer (ScIP) can be readily degraded in the solid state where the mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Xiao and coworkers [ 89 ] placed pyridyl disulfide-containing pendant groups on poly(benzyl ether) (PBE) backbones to form side chain-immolative polymers (ScIPs; Figure 23 ) which can be degraded upon exposure to reducing agents, such as DTT. These pendant groups were then reacted in a thiol-disulfide exchange reaction with either a mono-mercapto- terminated PEG (HS-PEG) or a bis-mercapto-terminated PEG (HS-PEG-HS), to produce a PEG-grafted ScIP (ScIP-g-PEG) or an extended network crosslinked by PEG groups via disulfide bonds ( Figure 24 ).…”
Section: Reaction Types and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Xiao and coworkers [ 89 ] placed pyridyl disulfide-containing pendant groups on poly(benzyl ether) (PBE) backbones to form side chain-immolative polymers (ScIPs; Figure 23 ) which can be degraded upon exposure to reducing agents, such as DTT. These pendant groups were then reacted in a thiol-disulfide exchange reaction with either a mono-mercapto- terminated PEG (HS-PEG) or a bis-mercapto-terminated PEG (HS-PEG-HS), to produce a PEG-grafted ScIP (ScIP-g-PEG) or an extended network crosslinked by PEG groups via disulfide bonds ( Figure 24 ).…”
Section: Reaction Types and Applicationsmentioning
confidence: 99%
“… Synthesis of PBE-based ScIPs bearing pyridyl disulfide pendant groups, and their reaction with mono-or bis-mercapto-terminated PEG to form PEG-grafted ScIPs (ScIP- g -PEG) or organogel networks with PEG-disulfide crosslinks. Adapted with permission from [ 89 ]. Copyright (2019) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…For example, Shabat and co-workers have shown that protecting groups can mask nucleophilic functionalities en route to water soluble poly(benzyl urethanes). 30 Zhang and co-workers have used post-synthetic disulfide metathesis 31 and 'click'-type reactions 32 to prepare SIP bottlebrushes and organogels. Gillies and co-workers have developed PPM strategies for preparing a range of functionalized polyglyoxylate and polyglyoxylamide SIPs via transesterification 33 and amidation reactions, 34 which significantly expand the functional scope of these polymers.…”
Section: Introductionmentioning
confidence: 99%